Optimasi Pengalokasian Sampah Wilayah Ke Tempat Pembuangan Sementara dengan Model Integer Linear Programming (Studi Kasus Kota Surakarta) - I Wayan Suletra; Eko Liquiddanu; Sigit Bagus Pamungkas (Performa: Media Ilmiah Teknik Industri, 2009)
This reserach proposes an integer linear programming model for the allocation of municipal solid waste to the optimal transfer station. This model involves trade-off between two kind of transportation cost, that is transportation cost from village to trasfer station and cost from transfer station to landfill/treatment center. Branch-and-bound method is used to find optimum decision, which transfer station should serve which village.This model is applied to city of Surakarta that consist of 596 village and 62 transfer stations. From analysis we know that this model can reduce total transportation cost per day by 5,38% and balances the accumulated waste in all trasfer station